2017
DOI: 10.1016/j.jjcc.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease and atrial fibrillation: An unknown relationship

Abstract: Chronic obstructive pulmonary disease (COPD) is independently associated with atrial fibrillation (AF). Decreased oxygenation, hypercapnia, pulmonary hypertension, diastolic dysfunction, oxidative stress, inflammation, changes in atrial size by altered respiratory physiology, increased arrhythmogenicity from nonpulmonary vein foci commonly located in the right atrium, and respiratory drugs have been implicated in the pathogenesis of AF in COPD. The understanding of the relationship between COPD and AF is of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 91 publications
4
91
0
5
Order By: Relevance
“…Additionally, we noted diabetes mellitus and chronic pulmonary disease to be associated with a high likelihood of AF recurrence. Our findings support the previously noted observation by Goudis24 that concurrent COPD in AF patients leads to worse outcomes in terms of AF progression, AF recurrence after catheter ablation, and overall mortality. Increased hospital volume for the catheter ablation predicted lower AF recurrence in our study, again highlighting the salubrious importance of increased institutional experience.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we noted diabetes mellitus and chronic pulmonary disease to be associated with a high likelihood of AF recurrence. Our findings support the previously noted observation by Goudis24 that concurrent COPD in AF patients leads to worse outcomes in terms of AF progression, AF recurrence after catheter ablation, and overall mortality. Increased hospital volume for the catheter ablation predicted lower AF recurrence in our study, again highlighting the salubrious importance of increased institutional experience.…”
Section: Discussionsupporting
confidence: 93%
“…Inflammation, decreased oxygenation, pulmonary hypertension, diastolic function impairment, oxidative stress, changes of atrial size leading to deformation may cause atrial conduction abnormalities including prolongation of atrial conduction times in patients with obstructive pulmonary disease. 13,14 In the present study, RV free wall thickness informing that RV systolic function was higher in asthmatic group. In several studies by Ghandi, Ghaderian and Shedeed et al, similar results were found that RV wall thickness significantly different between asthmatic patients and healthy subjects.…”
Section: Discussionsupporting
confidence: 55%
“…Echocardiographic abnormalities, such as left atrial enlargement,1516 left ventricular hypertrophy, and left ventricular systolic and diastolic dysfunction, have been associated with atrial fibrillation 1516171819. Other important risk factors include pulmonary diseases, such as obstructive sleep apnea and chronic obstructive pulmonary disease,2021 and systemic risk factors, such as hypertension, diabetes mellitus,1315 obesity,16 and cigarette smoking 22…”
Section: Incidence/prevalencementioning
confidence: 99%